2017
DOI: 10.2166/wrd.2017.091
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters of electrocoagulation/flotation process for removal of Acid Red 14 with mesh stainless steel electrodes

Abstract: Dyes are persistent compounds that are not easily biodegraded and are considered as carcinogenic.Electro-coagulation and electro-flotation method, due to its adaptability and compatibility with the environment, is regarded as one of the appropriate methods for the treatment of industrial wastewater containing dye. In this study in which stainless steel mesh electrodes with a horizontal arrangement are used, the most important parameters affecting the performance of the simultaneous system of electro-coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In general, the HCrO 4 – removal and current of the FESs gradually tended to be stable after 150 min. This phenomenon can be attributed to the adsorption of Cr species and formation of gas bubbles in the CFF electrodes, , which both gradually decreased the active areas for the electrochemical redox (current) , and inhibited the HCrO 4 – removal. As the operation time was increased, with the adsorption of Cr species becoming saturated, the gas bubbles were accumulated to certain volumes and moved along the flow direction by the flow effect, hence resulting in the dynamic equilibrium between bubble formation and flowing away (SI, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the HCrO 4 – removal and current of the FESs gradually tended to be stable after 150 min. This phenomenon can be attributed to the adsorption of Cr species and formation of gas bubbles in the CFF electrodes, , which both gradually decreased the active areas for the electrochemical redox (current) , and inhibited the HCrO 4 – removal. As the operation time was increased, with the adsorption of Cr species becoming saturated, the gas bubbles were accumulated to certain volumes and moved along the flow direction by the flow effect, hence resulting in the dynamic equilibrium between bubble formation and flowing away (SI, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical coagulation is efficient for sulfurous and disperse dyes. Acidic, direct, vat and reactive dyes coagulate with this method too, but do not settle, while cationic dyes do not even coagulate [18]. The conventional treatment methods such as activated sludge, coagulation and flocculation process, reverse osmosis and evaporation consume a lot of chemicals, high energy and are not sufficient to break down azo double bonds of reactive dyes.…”
Section: Existing Conventional Treatment Methods and Their Limitationsmentioning
confidence: 99%
“…However, an increase was observed in the conductivity values of Al and Fe electrodes between 0-20 min. In some EC studies, it has been reported that disinfectants or dissolved ions in wastewater may cause an increase in conductivity [21], [22]. Consequently, it is estimated that disinfectants or dissolved ions in HWW may have caused an increase in conductivity.…”
Section: Temperature and Conductivitymentioning
confidence: 99%